2017
DOI: 10.5539/ibr.v10n9p188
|View full text |Cite
|
Sign up to set email alerts
|

Who is Who? Identifying the Different Sub-groups of Secondary Stakeholders within a Community: A Case Study of the Niger Delta Region of Nigeria Communities

Abstract: The Nigerian oil and gas industry (NOGI) has over time been dominated by the Nigerian government and oil producing companies (OPCs). The influences of the community stakeholder on OPCs in the last three decades have been expressed in diverse ways by different community sub-groups through their concerns and interests, some of which have severely impacted on the NOGI. Community within this context is categorised as a primary stakeholder, while the sub-groups are secondary stakeholders that emerge from within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 116 publications
1
1
0
Order By: Relevance
“…All interviewees suggested that correctly identifying the right stakeholders and engaging them at the right time, is of paramount importance to the success of any project. This aligns with Osobajo and Moore (2017) assertion that identifying and having appropriate knowledge of the key stakeholders with respect to their intentions, interests, behaviour, influences and interrelations is essential for successful engagement. Likewise, Mitchell et al (1997) observed that considering relevant stakeholders based on one or more of the three relationship attributes of power, legitimacy and urgency will improve both the efficiency and effectiveness of the engagement process and intended outcomes.…”
Section: Case Study: Engaging Stakeholders From the Piraeus Cluster For Sustainable Developmentsupporting
confidence: 62%
See 1 more Smart Citation
“…All interviewees suggested that correctly identifying the right stakeholders and engaging them at the right time, is of paramount importance to the success of any project. This aligns with Osobajo and Moore (2017) assertion that identifying and having appropriate knowledge of the key stakeholders with respect to their intentions, interests, behaviour, influences and interrelations is essential for successful engagement. Likewise, Mitchell et al (1997) observed that considering relevant stakeholders based on one or more of the three relationship attributes of power, legitimacy and urgency will improve both the efficiency and effectiveness of the engagement process and intended outcomes.…”
Section: Case Study: Engaging Stakeholders From the Piraeus Cluster For Sustainable Developmentsupporting
confidence: 62%
“…It becomes crucial to identify and include all the relevant stakeholders as this will improve both the efficiency and effectiveness of the engagement process and intended outcomes. Osobajo and Moore (2017) added that identifying and having appropriate knowledge of the key stakeholders concerning their intentions, interests, behaviour, influences, and interrelations are essential for successful engagement. This is an essential step for maritime-related clusters, as to our experience, several related organisations are highly interest but less influential, and on the contrary, some organisations are not engaged but highly significant.…”
Section: Engagement Criteria For Sustainable Engagementmentioning
confidence: 99%